Development Trend of IP Router Tecbnologies - Huanan Chen; Yongjun Huang; Yongqing Zhu (Dianxin kexue)
Based on the IP router developing history,the most eye-tracking technologies of IP router were analyzed and discussed in-depth with the growing service requirements.The future routers should be high-volumed,virtualized,open-architected and programmable.As a result,the IP network is about to evolve to software-defined and cloud-network converged architecture.